FAKTOR PENENTU NIAT WAJIB PAJAK DALAM PENGGUNAAN APLIKASI CORETAX - Azzahra, Vira; Widayati, Neneng; Fauzi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aims to analyse the influence of perceived usefulness, perceived ease of use, perceived risk, and service quality on taxpayers’ intention to use Coretax as a digital tax administration system. The research employed a quantitative approach using Partial Least Squares Structural Equation Modelling (PLS-SEM) through SmartPLS v3.0 software. Data were collected from taxpayers via online questionnaires, then tested for validity, reliability, and hypothesis evaluation. The results indicate that among the four variables, only perceived risk has a significant effect on the intention to use Coretax, whereas perceived usefulness, perceived ease of use, and service quality are not significant. These findings highlight that in the context of digital tax administration, security and risk management are key determinants for system adoption. The study implies that tax authorities should focus on enhancing security, risk management, and providing education and practical demonstrations to increase user intention. Additionally, this research provides a foundation for future studies to explore other factors affecting the intention to adopt digital tax administration systems, including digital literacy and prior experience with online tax systems.